Does millet consumption contribute to raising blood hemoglobin levels compared to regular refined staples?: a systematic review and meta-analysis - Anitha, Seetha; Tsusaka, Takuji W.; Givens, D. Ian; Kane-Potaka, Joanna; Botha, Rosemary; Sulaiman, Nur Liana Binti; Upadhyay, Shweta; Vetriventhan, Mani; Rajendran, Ananthan; Parasannanavar, Devraj J.; Longvah, Thingnganing; Subramaniam, Kowsalya; et al. (Frontiers Media, 2024)
Millets are recognized for their health and nutritional values, and the United Nations declared 2023 the International Year of Millets. Among the several health and nutritional benefits of millets, their impact on hemoglobin concentration is important since anemia is a major public health issue in many countries. To investigate the effect of millet (including sorghum) consumption on hemoglobin concentration in the blood, a systematic review and meta-analysis were conducted. Thirteen published studies featuring randomized control trials involving 590 individuals in the intervention group and 549 control individuals were eligible for the meta-analysis. The difference-in-differences analysis revealed highly significant (p andlt; 0.01) positive effects of millet consumption on hemoglobin concentration, with an effect size of +0.68 standardized mean difference units. The change in hemoglobin concentration observed in the intervention group was +13.6%, which is statistically significant (p andlt; 0.0005), compared to that in the control group, which was +4.8% and not statistically significant (p = 0.1362). In four studies, the consumption of millets in the intervention group demonstrated a change from mild anemia to normal status among children, whereas there was no change in the control group. The findings provide evidence that the consumption of millets can improve blood hemoglobin concentration, likely resulting from increased iron intake. Further research is needed involving the assessment of iron content and bioavailability to better understand the effect variation among millet types and the mechanisms involved.